Attitude and Achievement of First-Year Chemistry Undergraduate Students at The University of the South Pacific - Johnson, Joel; Reddy, Pritika; Sharma, Sushita; Wakeling, Lara; Mani, Janice; Benveniste, Tessa; Naiker, Mani; Brown, Stephen (Frontiers in Education, 2022)
Student attitude toward chemistry may influence engagement and achievement in chemistry-related courses, however, equivocal results in studies conducted in Western countries to date indicate this relationship requires further investigation. In this study, we investigated the correlation between attitude toward chemistry and achievement amongst a cohort of first-year undergraduate students from The University of the South Pacific (USP). A cluster analysis was used to identify low- and high-achieving groups of students to further explore potential correlations. There was a positive correlation between the cognitive and affective components of attitude among low-achieving students, but not among high-achieving students. The cognitive component of attitude did not appear to be strongly correlated with achievement in students from either group, although the affective component was positively correlated with achievement. The single item most strongly correlated with student achievement was their response on the Worthless-Beneficial scale. One of the notable findings was the differences in the attitude-achievement relationship between low-achieving and high-achieving students, suggesting that combining these clusters of students into a single group for analysis may obscure underlying correlations. Chemistry educators should continue to target their teaching styles to cater to different learning styles and achievement levels of students, including cognitive and non-cognitive learning styles.